Evaluation of Adrenal Function in Nonhospitalized Patients with Cirrhosis - Maryam Moini (Canadian Journal of Gastroenterology and Hepatology, 2017)
Background. Patients with cirrhosis and advancing hepatic insufficiency may show various degrees of other organ malfunction, including brain, kidney, and lung. Several studies have also shown a high prevalence of adrenal insufficiency in cirrhotic patients that may cause hemodynamic instability. Materials and Methods. In this study we prospectively evaluated adrenal function in a population of nonhospitalized cirrhotic patients. Categorization of liver disease severity was done according to model for end-stage liver disease (MELD) score. Adrenocorticotropic hormone stimulation testing was performed on subjects using 250 μg of synthetic short acting hormone; radio immunoassay was used to measure plasma cortisol levels. Results. Of 105 cirrhotic patients, 15.23% had evidence of adrenal insufficiency. These patients were not statistically different from those with normal adrenal function in levels of serum creatinine or bilirubin, MELD score, or presence of cirrhosis related complications. Significant differences were seen in mean international normalized ratio and serum sodium. Patients with a sodium level < 135 mEq/L had a higher rate (31.25%) of adrenal insufficiency. Conclusion. Adrenal dysfunction was identified in a population of stable nonhospitalized cirrhotic patients. Our results suggest a possible role for adrenal dysfunction as a contributing factor in hyponatremia in cirrhosis independent of other known factors of neurohormonal activation secondary to systemic vasodilation.